Edna Aizenberg. On the Edge of the Holocaust: The Shoah in Latin America Literature and Culture. Waltham, Massachusetts: Brandeis UP, 2016. - Daniela Goldfine (Studies in 20th & 21st Century Literature, 2017)
Review of Edna Aizenberg. On the Edge of the Holocaust: The Shoah in Latin America Literature and Culture. Waltham, Massachusetts: Brandeis UP, 2016.
Keywords: Edna Aizenberg; On the Edge of the Holocaust: The Shoah in Latin America Literature and Culture